Simultaneously improving thermal conductivity and dielectric properties of poly(vinylidene fluoride)/expanded graphite via melt blending with polyamide 6. Issue 46 (5th July 2021) - Tong, Jun; Zhang, Haichen; Li, Wei; Chen, Haichu; Wang, Daoyong; Hu, Manfeng; Wang, Zhifeng
Abstract: Poly(vinylidene fluoride)/polyamide 6/expanded graphite (PVDF/PA6/EG) composite is prepared via one‐step melt extrusion. The EG is well dispersed with the addition of PA6 and mainly distributed in the PA6 phase due to the stronger affinity between them. As a result, the PVDF/PA6/EG sample presents higher dielectric permittivity than the PVDF/EG sample and maintain a low dielectric loss due to its sea‐island phase structure, which impedes the formation of conductive path in the composite. The mean interlayer spacing of the EG in the polymer matrix decreases obviously due to its improved dispersion state, which is in favor of the phonon transportation in the composite. As a result, the PVDF/PA6/EG sample exhibits a significantly improved thermal conductivity of about 0.48 W m −1  K −1, which is 140% higher than that of the PVDF sample and 37% higher than that of the PVDF/EG sample. Moreover, the PVDF/PA6/EG sample presents higher Young's modulus and tensile strength than the PVDF/EG sample. While the elongation at break of the PVDF/PA6/EG sample is only a little lower than that of the PVDF/EG sample. This means that the tensile properties of the composite are not destroyed obviously by melt blending with the immiscible PA6. Abstract : The dispersion state of expanded graphite in the composite is obviously improved after melt blending with PA6. The well dispersed expanded graphite is selectively distributed in the PA6 phase. As a result, the thermal conductivity and dielectric permittivity of the composite apparently enhanced due to the decreased mean interlayer spacing of EG. Moreover, the low dielectric loss can maintain low due to the sea‐island morphology structure of the composite.